2015
DOI: 10.1103/physreva.92.042711
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of experimental and theoretical electron-impact-ionization triple-differential cross sections for ethane

Abstract: We have recently examined electron-impact ionization of molecules that have one large atom at the center, surrounded by H nuclei (\ud H\ud 2\ud O\ud ,\ud \ud N\ud H\ud 3\ud ,\ud \ud C\ud H\ud 4\ud ). All of these molecules have ten electrons; however, they vary in their molecular symmetry. We found that the triple-differential cross sections (TDCSs) for the highest occupied molecular orbitals (HOMOs) were similar, as was the character of the HOMO orbitals which had a \ud p\ud -type “peanut” shape. In this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 37 publications
(39 reference statements)
0
16
0
Order By: Relevance
“…We used two theoretical methods to describe the present electron-impact ionization process. Although they have been described previously [35][36][37][38] we summarize the essential ideas and the particular ingredients for the current cases of interest in order to make this paper self-contained. More detailed information can be found in the references given.…”
Section: Theoretical Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used two theoretical methods to describe the present electron-impact ionization process. Although they have been described previously [35][36][37][38] we summarize the essential ideas and the particular ingredients for the current cases of interest in order to make this paper self-contained. More detailed information can be found in the references given.…”
Section: Theoretical Modelsmentioning
confidence: 99%
“…where the exchange-scattering T exc is calculated similar to T dir except that the particles 1 and 2 are interchanged in the final state wave function. To take the proper average (PA) over all molecular orientations [37], the TDCS is calculated for each orientation and then averaged over all possible orientations so that…”
Section: Theoretical Modelsmentioning
confidence: 99%
“…A summary of this work up to 2010 was given by Madison and Al Hagan [19]. More recently, studies have been performed for ionization of CH 4 [20], [21], tetrahydrofuran and tetrahydrofurfuryl [22], NH3 [23], the cyclic ethers tetrahydrofuran, tetrahydropyran and 1,4-dioxane [24], tetrahydropyran and 1,4-dioxane [25], phenol [26], N 2 [27], ethane [28], and furfural [29]. The M3DW has not been previously applied to CO 2 .…”
mentioning
confidence: 99%
“…However we think that it is still of interest to see how good or bad it is since it is very difficult (for us) to get access to enough computer time to perform the proper averages so it would be useful to know if there are cases where it can be used. So far, we have found that it is not good for some intermediate sized molecules [6], [18][19][20], but suprisingly a reasonably good approximation for the big molecules we have examined [21][22][23][24][25].…”
Section: Theoreticalmentioning
confidence: 99%